2015
DOI: 10.1002/cphc.201500883
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Molecular Coupling on Ultrafast Electron‐Transfer and Charge‐Recombination Dynamics in a Wide‐Gap ZnS Nanoaggregate Sensitized by Triphenyl Methane Dyes

Abstract: Wide-band-gap ZnS nanocrystals (NCs) were synthesized, and after sensitizing the NCs with series of triphenyl methane (TPM) dyes, ultrafast charge-transfer dynamics was demonstrated. HRTEM images of ZnS NCs show the formation of aggregate crystals with a flower-like structure. Exciton absorption and lumimescence, due to quantum confinement of the ZnS NCs, appear at approximately 310 and 340 nm, respectively. Interestingly, all the TPM dyes (pyrogallol red, bromopyrogallol red, and aurin tricarboxylic acid) for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3

Relationship

3
0

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 55 publications
2
2
0
Order By: Relevance
“…All the diffractograms match well with the crystal structure of bulk cubic zinc blend structure. , It can be seen that for CdSe, three major reflexes at 25.11°, 41.93°, and 49.66° appears due to the diffraction from (111), (220) and (311) planes, respectively. However, the diffraction from the same planes of large band gap ZnS appears significantly higher angles than CdSe which is well correlated with the previous literature . Interestingly both G-250 and G-300 alloy NCs show diffraction angles in between those of CdSe and ZnS NCs, viz.…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…All the diffractograms match well with the crystal structure of bulk cubic zinc blend structure. , It can be seen that for CdSe, three major reflexes at 25.11°, 41.93°, and 49.66° appears due to the diffraction from (111), (220) and (311) planes, respectively. However, the diffraction from the same planes of large band gap ZnS appears significantly higher angles than CdSe which is well correlated with the previous literature . Interestingly both G-250 and G-300 alloy NCs show diffraction angles in between those of CdSe and ZnS NCs, viz.…”
Section: Resultssupporting
confidence: 90%
“…However, the diffraction from the same planes of large band gap ZnS appears significantly higher angles than CdSe which is well correlated with the previous literature. 62 Interestingly both G-250 and G-300 alloy NCs show diffraction angles in between those of CdSe and ZnS NCs, viz. the diffractions from (111), (220), and (311) planes for G-250 appear at 25.43°, 42.57°, and 50.03°while those of G-300 appear at 25.35°, 42.41°, and 49.9°, respectively, which clearly suggests formation of alloy NCs.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…This is further supported by the stability measurement of both free and functionalized NCs for a few days (see Figure S10, Supporting Information). Earlier it was reported that a weaker coupling (e.g., salicylate or resorcinol) moiety leads to slower charge recombination than the stronger coupling (e.g., catechol) moiety in the semiconductor/molecule heterojunction, and therefore, the weakly coupled heterojunction may offer better charge separation. , In the present investigation, similarly, we believe due to weaker halogen–hydrogen coupling the recombination process between HQ and CsPbCl 3 NCs will slow down, making the CT process more efficient. In CsPbI 3 NCs, the stronger chelating coupling may be detrimental for photocatalysis and solar cells as it would lead to faster charge recombination; however, the unaltered PL emission may indicate a possible application toward LEDs for such coupling.…”
supporting
confidence: 60%
“…Thus, Zn and S get incorporated towards the core of the NCs along with other ions. Since Zn-based NCs have blue shifted absorption because of a large band gap, and the absorption of the G-300 alloy moves to the blue region as compared to the G-250 analogue, which indeed endorses the incorporation of Zn to the core of the NCs. Therefore, the absence of any core–shell-like arrangement, particularly the absence of inner core quasi-type-II behavior in G-300 alloy, results in no CT state formation.…”
Section: Exciton Dissociation In Mn-doped Ncs Through Electron Transfermentioning
confidence: 97%